2023
DOI: 10.1093/molbev/msad082
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomic Evidence of Adaptive Response during the Invasion History ofPlasmodium falciparumin the Americas

Abstract: Plasmodium falciparum, the most virulent agent of human malaria, spread from Africa to all continents following the out-of-Africa human migrations. During the transatlantic slave trade between the 16th and 19th centuries, it was introduced twice independently to the Americas where it adapted to new environmental conditions (new human populations and mosquito species). Here, we analyzed the genome-wide polymorphisms of 2,635 isolates across the current P. falciparum distribution range in Africa, Asia, Oceania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…French Guiana is located within the Guiana Shield region of South America and harbors a low P. falciparum endemicity that is concentrated in remote regions, particularly sites connected with gold mining (Musset et al 2014; Douine et al 2020). Movement of people and parasites throughout the Guiana Shield is well documented (Douine et al 2017; Mathieu et al 2021) and previous genetic clustering analyses of South American P. falciparum have shown that the Guiana Shield region harbors a genetically distinct parasite population (Yalcindag et al 2012; Carrasquilla et al 2022; Lefebvre et al 2023). P. falciparum gene flow therefore occurs across a region that is exposed to the varied public health measures in Brazil, French Guiana, Suriname, Guyana, and Venezuela (Sanna et al 2024).…”
Section: Resultsmentioning
confidence: 97%
“…French Guiana is located within the Guiana Shield region of South America and harbors a low P. falciparum endemicity that is concentrated in remote regions, particularly sites connected with gold mining (Musset et al 2014; Douine et al 2020). Movement of people and parasites throughout the Guiana Shield is well documented (Douine et al 2017; Mathieu et al 2021) and previous genetic clustering analyses of South American P. falciparum have shown that the Guiana Shield region harbors a genetically distinct parasite population (Yalcindag et al 2012; Carrasquilla et al 2022; Lefebvre et al 2023). P. falciparum gene flow therefore occurs across a region that is exposed to the varied public health measures in Brazil, French Guiana, Suriname, Guyana, and Venezuela (Sanna et al 2024).…”
Section: Resultsmentioning
confidence: 97%
“…Besides these observations, P. rodhain and P. schwetzi infection in humans has been demonstrated and shown to be successful through blood inoculations [5,23,30,62,65]. Infections of Chimpanzees with Plasmodium vivax and P. malariae have also been One Health Perspective of Malaria Transmission DOI: http://dx.doi.org/10.5772/intechopen.113908 demonstrated experimentally [60,64,66]. Another investigation into the prevalence of simian malaria identified P. falciparum, which was earlier thought to be a humanspecific species for malaria infections to have naturally infected Macaca radiata and Macaca mulatta in India [51].…”
Section: Emerging Zoonotic Malaria and Transmission Concernsmentioning
confidence: 88%
“…Recently, van Dorp et al [15] analyzed complete P. vivax nuclear genomes that included a composite sample from a ancient slide, and suggested a European introduction that coincided with the European colonization of Latin America. However, this study had important limitations, particularly (1) the absence of samples from West Africa, the region from where millions of enslaved persons were transported to Latin America during the transatlantic slave trade [16] and the source of American P. falciparum, another human malaria parasite [17][18][19]; (2) the European origin hypothesis relied only on a single, very low coverage, and composite sample originating from a multi-Plasmodium species co-infection (Ebro sample). Therefore, the possibility that the Ebro sample were of American origin and transferred back into Europe during the massive human movements between Europe and Latin America in the 19 th and 20 th centuries cannot be excluded, as suggested by Escalante et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…As more than seven million slaves, mainly from West/Central Africa, arrived in Central and South America during the transatlantic trade [16], it was imperative to consider West and Central African P. vivax populations to precisely determine the colonization history of P. vivax in Latin America. The relevance of an African origin must be taken into account because it has now been established that the colonization of Central and South America by Plasmodium falciparum , the most virulent human malaria agent, resulted from two independent introductions from West/Central Africa during the transatlantic slave trade [1719]. The high frequencies of Duffy-negativity in African populations, expected to protect against P. vivax infection might exclude such a hypothesis; however, the mounting evidence that P. vivax is present in West Africa [2022], as observed in Mauritania [23,24] and Senegal [25], reopens the door to this primary source.…”
Section: Introductionmentioning
confidence: 99%